Uji Efektivitas Poc Berbasis Limbah Rumah Tangga Pengganti Ab-Mix Dalam Budidaya Pakcoy Hidroponik - Desty Aulia Putrantri; Mustika Adzania Lestari; Annisa Fitri; Reza Zulfahmi; Desryan Irawan (Jurnal Penelitian Pertanian Terapan, 2026)
One environmentally friendly solution for managing household organic waste is converting it into Liquid Organic Fertilizer (LOF), which contains essential nutrients for plant growth. LOF not only improves soil fertility but also has the potential to serve as an alternative nutrient source in hydroponic systems, which are increasingly popular in urban agriculture. Since chemical fertilizers such as AB-Mix are relatively expensive, LOF offers a more economical and sustainable option, although its effectiveness and optimal concentration still require further evaluation. The objectives of this study were: (1) to determine the effect of household-waste-based LOF application on the growth of pak choi in a hydroponic system, (2) to determine the optimal concentration of household-waste-based LOF for pak choi growth in a hydroponic system, and (3) to evaluate the effectiveness of household-waste-based LOF as a substitute nutrient solution for pak choi growth in hydroponics. The research was arranged in a completely randomized design with four treatments, namely P0 = 100% AB-Mix (5 ml/L AB-Mix); P1 = 50% AB-Mix + LOF (2.5 ml/L AB-Mix + 5 ml/L LOF); P2 = 25% AB-Mix + LOF (1.25 ml/L AB-Mix + 5 ml/L LOF); and P3 = LOF (5 ml/L LOF). The observed variables included plant height, number of leaves, leaf greenness, fresh shoot weight, and fresh root weight. Based on the 5% Duncan test, the treatments showed significant differences in all observed variables. Treatment P0 produced the best response and was significantly different from the other treatments. Treatment P1 resulted in higher growth than P2 and P3, although statistically it was still significantly different from P0. Nevertheless, P1 demonstrated the ability to substitute AB-Mix nutrients by up to 50%.